PENERAPANSTRATEGI FLIPPED CLASSROOM DENGAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN MATEMATIKA DI KELAS XI SMKN 2 PADANGPANJANG - Eka Pasca Surya Bayu; Suci Mutia Rahmi (FKIP UMSB, 2018)
Based on the results of interviews of researchers with teachers of mathematics subjects who teach class XI SMKN 2 Padangpanjang obtained information that student learning outcomes are still low. Factors that affect the low learning outcomes of mathematics learners are the level of understanding of learners on the basis of mathematics is still lacking. One way to solve this problem is to apply the Flipped Classroom Learning strategy with the Saintik Approach to Mathematics Learning.The purpose of this research is